Investigation of the Properties of Concrete Made with Fly-Ash and Dry Waste Okra Powder - Rahmat, Y.; Abdulazeez, A. S.; Gambo, I.; Audu, I.; Isah, A. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Concrete is the most utilized construction material globally, with the issues of global warming, overburden and over-dependence on cement leads to the research into alternative materials in the production of concrete, which would not only reduce the usage of cement but also improve the performance of concrete product. The research investigates the effect of fly ash (FA) and dry waste okra powder (DWOP) on the strength performance of concrete. Concrete mix of 1:2.43:2.85 with water cement ratio of 0.5 was used. 10% by weight of cement was replaced by fly-ash, and dry waste okra powder was added at 0.25% to 1% at 0.25% interval as admixture. The parameters investigated are, chemical composition, setting time, workability, chemical composition of fly-ash and dry waste okra powder, density, compressive strength, flexural strength and split tensile strength. The results showed that fly-ash is a good pozzolan with combined SiO2, Al2O3 and Fe2O3 to equal 89.04%. The use of dry waste okra powder increases the setting time of cement/FA-DWOP paste and also resulted in the increase in workability of the concrete as the percentage admixture increases. The result showed that fly-ash ash has a pozzolanic effect and DWOP has an admixture effect on concrete properties by considering the strength activity index, higher compressive strength, higher flexural and splitting strength than control concrete for fly-ash blended admixture concrete at 0.5% and 0.75% up-to 1% admixture content. From this result, it can be concluded that FA as partial replacement material is a good pozzolanic material and DWOP is suitable as admixture material in concrete production.